TRADISI MANGAIN SEBELUM PERNIKAHAN PADA MASYARAKAT BATAK TOBA (Studi Kasus Di Desa Sungai Jaman, Kecamatan Tayan Hilir, Kabupaten Sanggau) - Hamid Ariansyah Tambunan; Marluwi Marluwi; Ishar Pulungan (Al-Usroh, 2025)
The tradition of Mangain (raising children), also means accepting someone foreign (not of the Batak tribe) to be like our own biological children by bearing a clan according to the Mangain clan. This research aims to find out: The procession of implementing the mangain custom before marriage in the Toba Batak community in Sungai Jaman Village, Tayan Hilir District, Sanggau Regency and Analysis of the implementation of the mangain tradition before marriage among the Batak Toba community in Sungai Jaman Village, Tayan Hilir Subdistrict, Sanggau Regency.This study uses a qualitative approach with descriptive and juridical-empirical methods. Data collection techniques were carried out through in-depth interviews with informants who were raja parhata (program guides) and several Toba Batak communities, as well as through documentation studies. Data were analyzed through data reduction, data presentation, verification, and conclusion drawing. Data validity was obtained through member check techniques by involving informants in validating data results. Based on the analysis conducted, the researcher concluded that: 1) the mangain tradition has several stages, namely: manghatai dohot par hula-hula (telling and asking the wife's family), pasada tahi (deliberation and consensus), mangain customary events (raising children), giving tudu sipanganon (food offerings), giving batu sipanganon (witness money), manulangi (feeding), sowing rice sipihir tondi (soul strengthener); 2). The mangain tradition practiced by the people of Sungai Jaman Village is classified as a unique al-urf or urf because it is only practiced by people in certain areas. The mangain tradition is also classified as urf shahih because it embodies a sense of kinship, maintains ties of friendship, and promotes religious tolerance.